STRESS –STRAIN DIAGRAM OF SELF-CONSOLIDATING CONCRETE SUBJECTED TO CHEMICAL ATTACK - M. Salman, Mohammed; J. Frayyeh, Qais; A. Zghair, Luma (Journal of Engineering and Sustainable Development, 2022)
Self-consolidating concrete (SCC) is increasingly used in a number of concrete applications, some of which are highly susceptible to attack by sulfuric acid. This work aimed to study the resistance of a wide range of different SCCs to sulfuric attack. The main variables studied included binder material type (highly reactive materials), limestone powder, and hybrid fibers in this work, compaction, L-box, and V-hopper were performed for the new mixtures. In this study, the specimens were immersed in a solution of sulfuric acid at a concentration (0.5%) for up to 289 days after normal curing for 28 days. Laboratory results show that concrete containing pozzolanic material has reduced mechanical properties compared to a mixture containing only limestone powder. The study also showed that there was an improvement in the resistance of concrete to acid solutions when hybrid fibers were added to the concrete mix. From the stress graph, the strain at given axial stress will be less than once the failure becomes more severe, it will become less rigid than immersing the specimen for six months.